Multivariate analysis of deboning data for classifying Hanwoo (Korean native cattle) by gender - Shim, Joon-Yong; Kim, Ha-Yeong; Cho, Byoung-Kwan; Yang, Seung Hwan; Mo, Changyeun; Do Kwon, Kyung; Kim, Jin-Hyoung; Lee, Wang-Hee (Current science (Bangalore), 2018)
Gender is an important factor in determining the market price of Hanwoo, but its discrimination is impossible after deboning. This study aims at identifying the variables in Hanwoo deboning data that could be used for gender identification and classification. Deboning data of Hanwoo were analysed by discriminant function analysis. Seven pre-deboning and 24 post-deboning variables were identified and showed 91.3% and 98.9% accuracy in gender identification respectively. Discriminant power was 98.9% on using all 31 deboning variables. This result suggests that physical characteristics of meat parts are suitable factors for classification of beef by gender.